Realizing individualized medicine: the road to translating proteomics from the laboratory to the clinic. (January 2011) - Rahbar, Amir; Rivers, Robert; Boja, Emily; Kinsinger, Christopher; Mesri, Mehdi; Hiltke, Tara; Rodriguez, Henry
The sequencing of the human genome has brought great promise and potential for the future of medicine, as well as providing a strong momentum for the burgeoning field of individualized medicine. Tests based on genetic information can be used to allow physicians to target therapies for those patients most likely to benefit from specific therapies and identify potential risk before the onset of disease. While advances in genomics-based molecular diagnostics are progressing, producing some useful US FDA-approved/-cleared diagnostic tests, protein-based molecular diagnostics have not met its promised potential. This article will provide an overview of protein-based analysis technologies, identify their strengths and limitations, discuss barriers to protein-based biomarker development and identify issues which must be addressed in order to successfully transfer the field of proteomics from the laboratory to the clinic.